파고지(Psoralea corylifolia)에서 분리한 isobavachalcone이 세포부착분자의 발현에 미치는 영향 - 이광민 (The Graduate School, Ajou University, 2014)
-ABSTRACT- Effect of IBC isolated from Psoralea corylifolia on expression of adhesion molecule-1 in cerebrovascular endothelial cells Kwang Min Lee Department of biomedical Sciences The Graduate School, Ajou University (Supervised by Associate Professor Soo Hwan Lee) Brain inflammation has been implicated in various cerebral diseases. Leukocyte-infiltration into brain parenchyma is critically associated with in the development brain inflammation. Therefore, control of leukocyte infiltration is a very important therapeutic target for the treatment of neurodegenerative diseases accompanied with inflammation such as Alzheimer’s disease and stroke. Isobavachalcone (IBC), a flavonoid from Psoralea corylifolia, is known to possess a wide spectrum of biological activities, antibacterial, antifungal, anticancer, anti-reverse transcriptase, antitubercular and antioxidant. Recently, it was reported that IBC suppresses LPS-induced iNOS expression and is expected to be useful for preventing or treating neurodegenerative disease. However, the effect of IBC on leukocyte-endothelial adhesion and expression of intercellular adhesion molecule-1(ICAM-1) in brain endothelial cells remains unexplored. In this study, we examined the effect of IBC on ICAM expression and leukocyte adhesion in bEnd.3 cells and explored the possible mechanisms therein involved. IBC significantly down-regulated LPS-induced ICAM-1 expression and leukocytes-endothelial adhesion. IBC suppressed LPS-induced sequential events for NF-kB activation, that is, IkB-α phosphorylation, p65 translocation into nucleus and NF-kB transcriptional activity. TLR4 conveys LPS-signal to intracellular compartment via MyD88- and TRIF-dependent pathways, which culminate in the activation of NF-kB. As well as, IBC attenuated MALP-2 (a TLR2, 6 specific ligand)-induced ICAM-1 expression, IkB-alpha phosphorylation and NF-kB transcriptional activation. suggesting inhibition of MyD88-dependent signaling pathway. IBC also down-regulated poly[I:C] (a TLR3 specific ligand)-induced expression of ICAM-1 and IFN-β, which was mediated suppression of NF-kB or IFN-β transcriptional activity, respectively. These data indicate TRIF-dependent signaling pathway is also blocked by IBC. Taken together, our data suggest that IBC inhibits LPS-induced ICAM-1 expression and leukocyte adhesion in brain endothelial cells and these effects are mediated by blockade of MyD88-dependent and TRIF-dependent signaling pathways and in turn, inhibition of NF-kB activity. -------------------------------------------------------- Key words : Isobavachalcone(IBC), Lipopolysacharide(LPS), intracellular adhesion molecule 1(ICAM-1), NF-kB, Inteferon-β(IFN-β), cerebrovascular endothelial cells(bEnd.3), Toll-like receptor4(TL
학위논문(석사)--아주대학교 일반대학원 :의생명학과,2014. 2
Keywords: Isobavachalcone(IBC); Lipopolysacharide(LPS); intracellular adhesion molecule-1(ICAM-1); NF-kB; Interferon-beta; cerebrovascular endothelial cell(bEnd.3); Toll-like recerptor4(TLR4)